Electronic Doping and Enhancement of n‐Channel Polycrystalline OFET Performance through Gate Oxide Modifications with Aminosilanes. Issue 16 (26th July 2021) - Shin, Nara; Schellhammer, Karl Sebastian; Lee, Min Ho; Zessin, Jakob; Hambsch, Mike; Salleo, Alberto; Ortmann, Frank; Mannsfeld, Stefan C. B.
Abstract: Self‐assembled monolayers (SAMs) are widely employed in organic field‐effect transistors to modify the surface energy, surface roughness, film growth kinetics, and electrical surface potential of the gate oxide to control the device's operating voltage. In this study, amino‐functionalized SAM molecules are compared to pure alkylsilane SAMS in terms of their impact on the electrical properties of organic field‐effect transistors, using the n‐type polycrystalline small molecule semiconductor material N, N ′‐dioctyl‐3, 4, 9, 10‐perylenedicarboximide (PTCDI‐C8). In order to understand the electronic impact of the amino groups, the effect of both the number of amino‐containing functional groups and the SAM molecular length are systematically studied. Though amino‐functionalized SAM materials have been studied previously, this study is, for the first time, able to shed light on the nature of the doping effect that occurs when the gate oxide is treated with polar aminosilane materials. By a comprehensive theoretical study of the interface on the molecular level, it is shown that the observed shift in the threshold voltage is caused by free charges, which are attracted to the PTCDI‐C8 and are stabilized there by protonated aminosilanes. This attraction and the voltage shift can be systematically tuned by varying the length of the neutral terminal chain of the aminosilane. Abstract : A set of amino‐functionalized self‐assembled monolayers (SAMs) are studied regarding their impact on the properties of organic field‐effect transistors (OFETs), analyzing both the number of amino groups and the SAM molecular length. By correlating the experimental data with theory, it is shown that the resulting OFET threshold voltage shifts are caused by mobile charges donated from the aminosilanes.